Guidelines to Develop Activities of Daily Living Skills in Children with Autism - มูลน้อย เจริญขวญั (Journal for Developing the Social and Community, 2019)
This article is related to the guideline to develop activities of daily living skills in children with autism. It is applicable for parents, families, caregivers and teachers of children with autism. The author studied from papers, textbooks and specialists in special education in order to apply the principles and techniques to develop activities of daily living skills in children with autism. The author actually used these guidelines to teach and practice. The selected guideline to develop activities of daily living skills in children with autism for parents. As for guideline to develop activities of daily living skills in children with autism for teachers, use the following techniques ; 1) Analyzing task technique, 2) TEACCH technique, 3) Demonstration technique, and 4) Positive reinforcement technique. These guidelines will help develop activities of daily living skills in children with autism, thus allow them to do daily living activities by themselves and be least dependent on others.